Extended Health Services of Pharmacists: Role in COVID-19 Management - Dahal, Sadhana; Khadka, Sitaram; Hashmi, Furqan K; Gupta, Ravi Prasad; Yadav, Tank Prasad; Adnan, Muhammad Abdul Jabar; Aryal, Pallav (Journal of Karnali Academy of Health Sciences, 2020)
COVID-19 is creating a chaotic scenario all over the world. Due to the unavailability of approved therapy, the number of affected cases is escalating day by day. Different components of the healthcare system have been consistently working in different settings for its containment. Pharmacists are one of the healthcare experts, who are working on the front-line. In this review, we aimed to evaluate the activities of pharmacists as a healthcare professional in disasters such as; COVID-19 management. The focus on services offered by pharmacists has shifted from traditional dispensing and compounding to patient-specific over a period contributing to the quality use of medicine and primary care. Pharmacists are thus, considered essentially one of the main pillars of the healthcare team for the provision of extended health services (EHS), for instance, the effective management of COVID-19. They are working from community to clinical setting. Practicing tele-pharmacy health services, they can reach out to remote places as well. Utilizing their expertise on clinical as well as managerial aspects, they have proved to be dynamic professionals in such a global health crises. Adequate training, inclusion of disaster management in the curriculum of pharmacy, support from the legislative body, and inter- as well as intra-professional collaboration are the key factors for professional development and recognition.